Financial Development, Financial Openness, and Economic Growth - Gemma Estrada; Donghyun Park; Arief Ramayandi (Asian Development Bank (ADB), 2015)
A sound and efficient financial system is an indispensable ingredient of economic growth. It consists primarily of banks and capital markets, which channel savings into investments and other productive activities that contribute to economic growth and augment the economy's productive capacity. This paper explains the importance of financial development and openness. It sifts through the literature on the relationship between both variables and economic growth. It then reports the results and discusses some original empirical analysis. In addition to using more updated data, which extend the sample period to include some postcrisis years, the analysis examines whether country characteristics and factors such as the exchange rate regime affect the finance-growth nexus.
hdl:11540/5104
Keywords: C33; E44; F31; G20; 330; economic growth; exchange rate regime; financial development; financial openness